Entre o mesmo e o outro: a ambiguidade do conceito de renovação - Cavalheiri, Alceu (2018)
The general objective of this research is to investigate the theme of the renovation of man and Western culture or of philosophy itself, presented at the beginning of the 20th century by Edmund Husserl (1859-1938) and Emmanuel Lévinas (1906-1995). Historical events, especially those in the late nineteenth and early twentieth centuries, driven by technological euphoria, but, also, by military conflicts, economic and moral miseries, revealed the absurdities practiced against humanity. The autonomous freedom of the science of knowing and transforming has not been able to respond to the meaninglessness of life or to heal the miseries of humanity. Therefore, this lack of response to the meaning of man's life is the motive that leads to investigate the proposals of Husserl and Lévinas, which question the way of doing science and also its meaning for humanity, proposing an ethical human thought. In this sense, the thesis is that ethics is inserted in a perspective of renovation, both in Husserl's proposal and in that of Lévinas. In view of this, it begins with the Lévinasian realization that philosophy has always been involved with the search for truth movement, which can be accessed both by the dynamics of identity (itself) and/or, through the movement of otherness (other). The dynamics of identity is the universal path of free and autonomous inquiry, in which sensitive, instinctive, and even transcendent adversities are reduced to reason or made indifferent, unfounded and meaningless. In this bias, the experience of truth is free inquiry, to the molds of reason. In the movement of otherness, the path of inquiry departs from the subjective world, towards the unusual. External adversities are not reduced to reason and research implies responsibility, since the search for truth directs the researcher to transcendence and, therefore, heteronomous movement in which the different remains different in absolute and the experience of truth a path of approximation. Thus, the problem of research lies in the fact that the proposal for the renovation of philosophy confronts the two possible paths in the very movement of philosophical thinking, making the process of renewal a possibly ambiguous movement. Understanding that renovation is the movement to retake the elementary of philosophy, then the thesis that ethics is inserted in this movement revolves around the problem of knowing in which of the ways ethical human thinking can be ethically returned. Therefore, the possibility of an approximation between the concepts of work and renovation is observed, since both Husserl and Lévinas propose a new subjective attitude from the ethical movement. According to Lévinas, the work is the movement of subjectivity, of single and fraternal orientation, which goes from the same to the other with responsibility. And, according to Husserl, renovation is the subjective process of self-determination and self-discipline that guides ethical life. So both the work and the renovation refer to an ethical movement in which the self does not remain indifferent and selfish, but encouraged to leave and renew itself. Ethics is inserted in the movement of renewal of philosophy.